2022
DOI: 10.3390/ijerph192114215
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Health-Related Fitness and Quality of Life in Nonalcoholic Fatty Liver Disease

Abstract: Background: It is well known that patients with nonalcoholic fatty liver disease (NAFLD) suffer from impaired quality of life (QoL) and decreased health-related fitness. Studies on the relationship between them have been scarce. Methods: A cross-sectional survey was performed in 104 NAFLD patients. Liver fat content and fibrosis were assessed using transient elastography. Health-related fitness was measured by fitness test. VO2max was determined by YMCA submaximal cycle ergometer test. Body composition was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…When faced with this situation, taking the first step toward exercising may be helpful, such as putting on sneakers and going outdoors. A few patients mentioned struggling with poor physical fitness and ability; this reason was supported by some studies showing that patients with NAFLD have a lower physical function and performance status (26). Additionally, patients with NAFLD experience perceived exertion more frequently when exercising at similar intensities to those with chronic hepatitis C (27).…”
Section: Discussionmentioning
confidence: 94%
“…When faced with this situation, taking the first step toward exercising may be helpful, such as putting on sneakers and going outdoors. A few patients mentioned struggling with poor physical fitness and ability; this reason was supported by some studies showing that patients with NAFLD have a lower physical function and performance status (26). Additionally, patients with NAFLD experience perceived exertion more frequently when exercising at similar intensities to those with chronic hepatitis C (27).…”
Section: Discussionmentioning
confidence: 94%
“…Wang et al also pointed out the association between NAFLD and the deteriorating health-related quality of life in the context of reduced physical mobility, underscoring the complexity of the problems faced by those with the condition [24]. Their study on quality of life suggested that interventions were necessary to reduce the VFA and increase muscle mass [24].…”
Section: Discussionmentioning
confidence: 99%
“…The observed interconnections between hypothyroidism and metabolic disturbances manifesting in the liver and body composition have not yet been comprehensively analyzed in the context of lifestyle. Furthermore, the quality of life of individuals with coexisting NAFL and hypothyroidism, which diminishes when analyzed separately, has not been assessed [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%